Role of human factor for the implementation of the “Vision Zero” concept in railway transport: An overview - Muhammad Azri, Muhammed Nor; Jaganathapillai, T.; Ahmad Fitri, Yusop; Mohd Adnin, Hamidi; N. A., Abdul Hamid; W. M., Wan Mohamed (AIP Publishing, 2023)
The railway is an essential mode of transportation. Despite advances in railway safety over the past few decades, train accidents and incidents continue to be prevalent. From statistical data around 80% of railroad accidents are caused by human error. Consequently, the study of human reliability is necessary, and it must be included within a complete reliability assessment for every railway-related system. The needs of human reliability analysis considered as an important criterion for the smooth and zero injuries operation in the complex Railway systems. The European standard EN 50126 emphasizes that human reliability is a necessary element for railway engineering. In this study of human reliability and analysis specifically a study on driver profile of an electric train. Within a complete driving operation, railway drivers are presented with a variety of error-producing conditions. These circumstances, when paired with essential human characteristics, lead to a variety of errors. Many accidents and mishaps in complex systems, including the railway system, are caused by human error. The purpose of this paper is to determine human factors influence the degree of occupational injuries by accidents. Besides that, some motivating aspects of human factor in a way that enables the concept of zero injuries in Railway Transportation Industry are introduced.